2005
DOI: 10.1001/archopht.123.6.729
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Objective Perimetry Using Multifocal Visual Evoked Potentials in Glaucoma Practice

Abstract: Objectives: To evaluate the role of objective perimetry using multifocal visual evoked potentials (mVEPs) in glaucoma practice, and to assess its utility in patients with inconclusive standard automated perimetry findings. Method: A retrospective case series of 436 consecutive subjects referred for glaucoma investigation who underwent testing with the AccuMap V1.3 mVEP system (Ob-jectiVision Pty, Ltd, Sydney, New South Wales, Australia) within a defined 12-month period. Sensitivity was determined by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 16 publications
1
60
0
1
Order By: Relevance
“…A number of studies have demonstrated an ability to detect glaucomatous damage using multifocal visual evoked potentials (mfVEP) (Klistorner et al, 1998;Graham et al, 2000;Hood et al, 2000;Hasegawa et al, 2001;Goldberg et al, 2002;Hood and Greenstein, 2003;Thienprasiddhi et al, 2003;Hood et al, 2004;Graham et al, 2005), positron emission tomography (PET) (Kiyosawa et al, 1989), and single photon emission computed tomography (SPECT) Yoshida et al, 2006). Each technique has its limitations.…”
Section: Prior Investigations Of Cortical Activity In Human Glaucomamentioning
confidence: 99%
“…A number of studies have demonstrated an ability to detect glaucomatous damage using multifocal visual evoked potentials (mfVEP) (Klistorner et al, 1998;Graham et al, 2000;Hood et al, 2000;Hasegawa et al, 2001;Goldberg et al, 2002;Hood and Greenstein, 2003;Thienprasiddhi et al, 2003;Hood et al, 2004;Graham et al, 2005), positron emission tomography (PET) (Kiyosawa et al, 1989), and single photon emission computed tomography (SPECT) Yoshida et al, 2006). Each technique has its limitations.…”
Section: Prior Investigations Of Cortical Activity In Human Glaucomamentioning
confidence: 99%
“…Scotomas can be identified, and field defects in glaucomatous optic neuropathy and optic neuritis have been well defined. (Klistorner et al, 2000;Hood et al, 2000Hood et al, , 2003Hood et al, , 2004Goldberg et al, 2002;Graham et al, 2005) The mfERGs and multifocal visual evoked potentials (mfVEPs) recorded from a patient who developed an acute visual field loss after vitrectomy are shown in Figure 13. (Shinoda et al, 2000) The patient had undergone uncomplicated vitrectomy for a long-lasting vitreous hemorrhage associated with proliferative diabetic retinopathy.…”
Section: Multifocal Vep and Its Clinical Applicationsmentioning
confidence: 99%
“…2,11,13,19 and in glaucoma suspect eyes with completely normal SAP VFs. 4,5,9,14,18,19 Longitudinal follow-up should reveal whether such mfVEP defects represent greater sensitivity of the mfVEP to detect early functional loss, or alternatively, a higher false alarm rate. Meanwhile, cross-sectional studies have found that the diagnostic performance of mfVEP and SAP are similar when an independent diagnostic standard is applied (eg, one based on optic disc structure).…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although most of these studies have demonstrated close agreement between mfVEP and standard automated perimetry (SAP), some have shown that mfVEP abnormalities appear in regions (eg, hemifields) of the VF that have normal sensitivity on SAP, 2,11,13,19 and in glaucoma suspect eyes with completely normal SAP VFs. 4,5,9,14,18,19 Longitudinal follow-up should reveal whether such mfVEP defects represent greater sensitivity of the mfVEP to detect early functional loss, or alternatively, a higher false alarm rate. Meanwhile, cross-sectional studies have found that the diagnostic performance of mfVEP and SAP are similar when an independent diagnostic standard is applied (eg, one based on optic disc structure).…”
mentioning
confidence: 99%
See 1 more Smart Citation